Feminim -Transformational: Types of Women's Leadership in Adiwiyata School Development at SDN Bhayangkara Yogyakarta - Zakiatus Syarifah; Zainal Arifin; Fitria Wulandari (Jurusan PGMI FTIK IAIN Metro Lampung, 2021)
Abstract Leadership can be carried out by male or female figures based on the suitability of their competencies with the needs of the organization. The benchmark for leadership success is if in the process it directs and moves all members to achieve organizational goals. Through this research, we will discuss the types of women principals' leadership in the development of adiwiyata schools. This research is a qualitative research conducted at SDN Bhayangkara Yogayakarta. The findings of this study are: 1) The leadership type of female principals at SD N Bhayangkara Yogyakarta is feminine-transformational, 2) As an effort to develop adiwiyata schools at SDN Bhayangkara Yogyakarta by the principal, namely the application of four indicators, then exemplary, and involving the active participation of parents in developing adiwiyata schools, 3) The supporting factors are sourced from the leadership, namely the principal competence , school management team, and other human resources such as the community, parents and government, as well as the availability of resources such as adequate land . However, there are inhibiting factors originating from the lack of personal initiative from school residents and also the high level of idealism in the administration of adiwiyata Keywords: feminine-transformational , leadership, women, adiwiyata school Abstrak Kepemimpinan dapat dilakukan oleh tokoh laki-laki atau perempuan berdasarkan kesesuaian kompetensinya dengan kebutuhan organisasi. Tolok ukur keberhasilan kepemimpinan adalah jika dalam prosesnya mengarahkan dan menggerakkan seluruh anggota untuk mencapai tujuan organisasi. Melalui penelitian ini akan dibahas tipe-tipe kepemimpinan kepala sekolah perempuan dalam pengembangan sekolah adiwiyata. Penelitian ini merupakan penelitian kualitatif yang dilakukan di SDN Bhayangkara Yogayakarta. Temuan penelitian ini adalah: 1) Tipe kepemimpinan kepala sekolah perempuan di SD N Bhayangkara Yogyakarta adalah feminin-transformasional, 2) Sebagai upaya pengembangan sekolah adiwiyata di SDN Bhayangkara Yogyakarta oleh kepala sekolah yaitu penerapan empat indikator, maka keteladanan, dan melibatkan peran aktif orang tua dalam mengembangkan sekolah adiwiyata, 3) Faktor pendukung bersumber dari kepemimpinan yaitu kompetensi kepala sekolah, tim pengelola sekolah, dan sumber daya manusia lainnya seperti masyarakat, orang tua dan pemerintah, serta ketersediaan sumber daya seperti lahan yang memadai. Namun terdapat faktor penghambat yang berasal dari kurangnya inisiatif pribadi dari warga sekolah dan juga tingginya idealisme dalam penyelenggaraan adiwiyata. Kata kunci: Transformasi feminin, kepemimpinan, perempuan, sekolah adiwiyata